A Different Approach to Legislative Bodies: Reﬂections on the History of Parliament Oral History Project and Laws Around Abortion - Emma Peplow; Priscilla Pivatto (Rechtsgeschichte - Legal History)
The History of Parliament Oral History Project has been interviewing former Members of the UK Parliament since 2011. Life stories from inside Parliament reveal missing information about personal motivations, informal cross-party collaboration and use (and misuse) of procedure that helps to demonstrate both how the institution worked and the difficulties of writing and passing legislation. Oral history interviews can be used as a source to add different perspectives on legal history, encouraging researchers to challenge more traditional sources. The paper discusses memories of some controversial legislation where individuals have deeply-held beliefs: laws around abortion. This is an example of how oral history can be used to understand the complexities of the process of law making and how things are done inside an institution, while also providing some personal and human perspectives on Parliament.